Antioxidant Extracts from Greek and Spanish Olive Leaves: Antimicrobial, Anticancer and Antiangiogenic Effects - Ioana Zinuca Magyari-Pavel; Elena-Alina Moacă; Ștefana Avram; Zorița Diaconeasa; Daniela Haidu; Mariana Nela Ștefănuț; Arpad Mihai Rostas; Delia Muntean; Larisa Bora; Bianca Badescu; Cristian Iuhas; Cristina Adriana Dehelean; et al. (MDPI AG, 2024)
Olea europaea L. is the most valuable species of the Olea type, and its products offer a wide range of therapeutical uses. The olive tree has been extensively studied for its nourishing qualities, and the "Mediterranean diet", which includes virgin olive oil as a key dietary component, is strongly associated with a reduced risk of cardiovascular disease and various malignancies. Olive leaves, a by-product in the olive harvesting process, are valued as a resource for developing novel phytomedicines. For this purpose, two ethanolic extracts obtained from Olivae folium from Spain (OFS) and Greece (OFG) were investigated. Our findings contribute to a wider characterization of olive leaves. Both extracts displayed important amounts of phenolic compounds and pentacyclic triterpenes, OFG having higher concentrations of both polyphenols, such as oleuropein and lutein, as well as triterpenes, such as oleanolic acid and maslinic acid. The antioxidant capacity is similar for the two extracts, albeit slightly higher for OFG, possibly due to metal polyphenol complexes with antioxidant activity. The extracts elicited an antimicrobial effect at higher doses, especially against Gram-positive bacteria, such as Streptococcus pyogenes. The extract with lower inorganic content and higher content of polyphenols and triterpenic acids induced a strong anti-radical capacity, a selective cytotoxic effect, as well as antimigratory potential on A375 melanoma cells and antiangiogenic potential on the CAM. No irritability and a good tolerability were noted after evaluating the extracts on the in vivo Hen's Egg Test−Chorioallantoic Membrane (HET-CAM). Therefore, the present data are suggestive for the possible use of the two types of olive leaf products as high-antioxidant extracts, potentially impacting the healthcare system through their use as antimicrobial agents and as anticancer and anti-invasion treatments for melanoma.